Learning Models in Educational Game Interactions: A Review - Aulia Akhrian Syahidi; Ahmad Afif Supianto; Tsukasa Hirashima; Herman Tolle (International Journal of Engineering Education, 2021)
Educational games have now been used as innovative media and teaching strategies to achieve more effective learning and have an impact that tends to be very good in the learning process. However, it is important to know and systematically prove that the application of the learning model in the interaction of educational games is indeed feasible to be adopted and has an effect. This paper aims to present empirical evidence of the current situation regarding the application of learning models in the flow of educational game interactions. The method used is a systematic literature review by adopting three main stages, namely: 1) Planning; 2) Implementation; 3) Reporting. Then recommend the ten steps in the systematic literature review process along with the selection process through the test-retest approach. The initial search obtained 1,405,310 papers, then go through the selection stage. The selection process took place at stage B1 with the number of papers that successfully passed 198, at the B2 selection stage there were 102 papers, and we focus 75 papers that have passed a fairly rigorous screening and selection process on the quality assessment process for primary studies, used to answer research objectives and questions. We can confirm and conclude that 75 papers have applied the learning model in educational game interactions. The dominating domain is Education, the type of game that dominates is Educational Game, for the most dominating subjects are Programming, Student Learning Motivation as the most dominating impact, Experimental Design as a trial technique, the most widely used evaluation instruments are Questionnaires and Tests, a population that dominates between 79-2,645 people, and 8 papers to support learning in vocational education.